The impact of destination attributes on Muslim tourist's choice - Mohamed Battour; Mohd Nazari Ismail; Moustafa Battour (John Wiley & Sons, Ltd., 2024)
The success of marketing destinations for Muslim tourists could be guided by observing Islamic teachings in tourism activities. This study is a trial to explore which Islamic attributes of destinations could be used a base for tailoring Halal tourist packages. Qualitative data were collected by conducting two focus group discussions and fifty three interviews in Malaysia. Two major aspects are identified which may attract Muslim tourists. Some suggestions are also presented to satisfy Muslim tourists.